Low-speed recovery in euroland - Joachim Benner; Klaus-Jürgen Gern; Carsten-Patrick Meier; Joachim Scheide (Institut für Weltwirtschaft (IfW), 2005)
The economic recovery in the euro area lost momentum in 2004. After a strong increase during the first half, real GDP rose at an annual rate of less than 1 percent in the following two quarters. Overall capacity utilization, which had increased in the first half of 2004 for the first time in several years, fell once again. While internal demand picked up somewhat, the weakening of export growth could not be compensated. In the wake of the renewed weakness, labor market conditions did not improve. Inflation accelerated at the end of last year because of the surge in oil prices. High oil prices and the strength of the euro will dampen the economic expansion for a while, so the recovery will continue to be rather modest during the first half of 2005. Later on, the negative effects will fade, and economic activity will accelerate somewhat. We expect real GDP to increase by 1.4 percent in 2005; the unemployment rate will remain high. Next year, the recovery will gain further momentum also because monetary policy will remain expansionary; we expect that the ECB will not raise key interest rates very soon. Real GDP growth will amount to 2.0 percent in 2006, and the unemployment rate will drop to 8.3 percent. Inflation will remain slightly below 2 percent in both years. The situation of public finances has deteriorated further. In 2004, the aggregated budget deficit rose to 2.9 percent of GDP, compared to 2.7 percent last year. In addition to Germany, France, the Netherlands, and Greece, the deficit ratio probably exceeded the 3 percent margin also in Portugal. Several governments will apparently not consolidate their budgets as intended by the Stability and Growth Pact (SGP). In the recently published Stability Programs, the budgets of several large countries are not projected to be balanced until 2008, even though growth assumptions appear very optimistic. In March this year, the European governments and the European Commission decided on changes in the implementation of the Stability and Growth Pact. They imply that budget deficits will be higher in the future and that the debt-to-GDP ratios will continue to rise. One reason for this is that countries can now claim special circumstances, which means that a deficit ratio above 3 percent will not automatically be called excessive. Furthermore, countries with high deficits should consolidate their budgets mainly in good times, which are defined as years in which the output gap is positive. And they are given more time than before to take corrective actions. All in all, the sustainability of public finances will deteriorate. The main target of the SGP - to balance the budgets in the medium term and to reduce government debt to below 60 percent of GDP at a satisfactory pace - will not be achieved.
Keywords: 330; Konjunktur; Konjunkturprognose; Reform; Europäische Wirtschafts- und Währungsunion; EU-Staaten